Blossom and bee pollen from Rosa rugosa as potential intervention for acne caused by excessive androgen secretion in golden hamster acne model. Issue 1 (1st January 2019) - Zhao, Liang; Qiu, Jiafei; Yin, Xiaoting; Zhang, Nanhai; Wu, Wei; Wang, Chengtao; Ji, Baoping; Zhang, Liebing; Zhou, Feng
ABSTRACT: In this study, we determined the nutritional and functional components in blossom and bee pollen from Rosa rugosa and evaluated their effects on acne caused by excessive androgen secretion based on the golden hamster acne model. Blossom and bee pollen extract from Rosa rugosa had beneficial effects on reducing the area of the sebaceous glands, decreasing TG levels in the sebaceous glands, decreasing the release of IL-1α and TNF-α, alleviating the release of MMP-2 and MMP-9, increasing the content of caspase-3, reducing the release of testosterone T, and increasing the release of estrogen E2 . Both blossom and bee pollen extract from Rosa rugosa could alleviate acne caused by excessive androgenic secretion. In addition, bee pollen extract may have better effects on alleviating the release of inflammatory cytokines and MMPs, and promoting the degree of apoptosis. However, blossom extract may have better effects on regulating the levels of sex hormone.